2012
DOI: 10.1002/pi.4288
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chain structure and morphology of an olefinic blocky copolymer and a Ziegler–Natta‐based ethylene random copolymer

Abstract: The microstructure and morphology of an olefinic blocky copolymer (OBC) and an ethylene‐hexene copolymer prepared by conventional Ziegler‐Natta catalysis (ZNEH) are compared. It is found that these two samples have similar melting temperatures, but the overall comonomer content in OBC is slightly higher. The crystallization temperature and crystallinity of OBC are markedly lower than those of ZNEH. A successive self‐nucleation annealing experiment reveals that OBC has a more uniform distribution of crystal thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…It was observed that in melts, following perturbations occurring during the sample preparation, a fraction of the molecules with a large mismatch in block length are driven away from the lamellar interface and swell the domain preferred by the longer blocks (Hustad et al, 2009). It was also observed that more amorphous phases are rejected outside of the lamellar stacks (Tong et al, 2012). Thus, it was demonstrated (Jin et al, 2010) that smaller perturbations favor the expelling of unbalanced molecules for which the entropy lost by the longer block opposes the enthalpy gained by surrounding the short blocks with similar segments.…”
Section: Figure 10mentioning
confidence: 99%
“…It was observed that in melts, following perturbations occurring during the sample preparation, a fraction of the molecules with a large mismatch in block length are driven away from the lamellar interface and swell the domain preferred by the longer blocks (Hustad et al, 2009). It was also observed that more amorphous phases are rejected outside of the lamellar stacks (Tong et al, 2012). Thus, it was demonstrated (Jin et al, 2010) that smaller perturbations favor the expelling of unbalanced molecules for which the entropy lost by the longer block opposes the enthalpy gained by surrounding the short blocks with similar segments.…”
Section: Figure 10mentioning
confidence: 99%
“…5,6 The innovation of "chain shuttling polymerization" (CSP), in comparison to conventional ethylene/α-olefins copolymerization with Ziegler-Natta catalysts, lies in the use of "chain shuttling agents" (CSAs), which enable the shuttling of growing chains between different active catalyst centers. [5][6][7] The blocky nature of OBCs originates from hard crystallizable ethylene segments, at the same time, soft blocks with higher comonomer content that allow for producing copolymer chains with a new range of physical, mechanical, thermal, and rheological properties. [8][9][10][11][12][13][14][15][16] The architectural features of OBCs such as hard block fraction, average block length, and difference in comonomer content of blocks, can be controlled in the course of CSP process by careful selection of the feeding strategy of catalyst, CSA, and monomer, respectively.…”
mentioning
confidence: 99%
“…Comparing the l a s of SEPs, OBCs and ZNEH, we notice that the l a s of SEPs are evidently smaller than those of OBCs (∼20 nm) 28 and ZNEH (∼15 nm). 29 This reveals that the noncrystalline segments in SEPs are shorter than those in both OBCs and ZNEH, which may originate from the rapid oscillation of the unbridged metallocene.…”
Section: Resultsmentioning
confidence: 97%
“…28 On the other hand, no clear spherulitic structure can be identified in ZNEH, though the lamellae are densely stacked. 29 The POM and TEM characterizations reveal that the crystals of SEP14 are less perfect than those of OBC-A, but more ordered than those in ZNEH. Similarly, the crystals of SEP26 are not so ordered as those in OBC-B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation